Chloride Processing Of Metal Sulphides: Review Of Fundamentals And Applications (The Minerals, Metals and Materials Society, 2003)
The physico-chemical principles of chloride hydrometallurgy are reviewed to rationalise the complex chemistry in chloride-based processes for metal sulphides in terms of the predicted Eh-log[Cl-] relationships, measured changes in activity of H+, Mz+, Cl- and solubility of Ag(I), Cu(I), Cu(II), Pb(II), Ni(II), Au(III), Sb(III) and Bi(III). These changes reflect the nature of chemical speciation, competing effect of hydration/hydrolysis and chloro-complexation,composite effect of increasing acid and/or salt concentration and decreasing water activity. Rate data for the dissolution of PbS and ZnS in HCl containing Fe(III) or Cu(II) are compared and contrasted to highlight the effect of acid and chloride concentration, water activity, and the nature of oxidant. It is shown that LiCl, NaCl and HCl influence the kinetics of oxidative PbS leaching based on their effect on solubility of PbCl2 co-precipitated with elemental sulphur on the mineral surface. Evidence for the beneficial effect of Cu(II) in sulphide leaching is discussed.